(untitled) (Revista Contexto & Educação, 2024)
This article presents the results of the work that aimed to investigate the teaching and learning processes of the spanish language, in the spanish language course, remotely developed using the WhatsApp platform as a teaching tool, together with the portuguese and spanish literature faculties of the nature and culture institute (NCI) of the federal university of Amazonas (FUAM). In that regard we proceeded methodologically using a 15 questions questionnaire, among them, 07 of them were close and 08 of them were open, all formulated by the Google Forms and applied for 42 students, in which 24 responded the questionnaire. Our analysis were based on the questionnaire and on Borges and Paiva (2011), Kunski (2012), Có et al. (2020), Araújo e Bottentuit Junior (2015) reflexions, as well as the content analysis (BARDIN, 2016) organized in 3 analysis procedures steps. 1) pre-analysis; 2) material exploration and 3). The first category is about the participants of the research; the second is related to internet and connectivity; the third is related to the use of WhatsApp as a teaching platform and the fourth, is related to the teaching and learning of the Spanish language in the remote modality. With that, we are going to be able to identify the difficulties faced by the students of the remote learning method.